1994
DOI: 10.1016/0735-1097(94)90290-9
|View full text |Cite
|
Sign up to set email alerts
|

Progressive decreases in coronary vein flow during reperfusion in acute myocardial infarction: Clinical documentation of the no reflow phenomenon after successful thrombolysis

Abstract: Salvage of myocardium from infarction by successful thrombolysis was not observed in the patients demonstrating progressive decreases in great cardiac vein flow (group A). In those patients, inadequate myocardial reperfusion on a microvascular basis might be associated with a much larger myocardial infarction. Antecedent angina may protect against a progressive decrease in coronary flow and may have beneficial effects on infarct size limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 46 publications
0
23
0
1
Order By: Relevance
“…85 In another clinical study, patients with no reflow were older and had a lower incidence of preinfarction angina. 86 The absence of preinfarction angina was also noted in the series of Komamura et al 84 This may be related to the concept that the presence of preinfarct angina is associated with smaller infarcts and a possible preconditioning-like effect and may correlate with collateral formation. 87 The no-reflow phenomenon was also linked to ventricular arrhythmias, 88 early congestive heart failure, 89 and even cardiac rupture.…”
Section: Clinical Presentationmentioning
confidence: 70%
See 1 more Smart Citation
“…85 In another clinical study, patients with no reflow were older and had a lower incidence of preinfarction angina. 86 The absence of preinfarction angina was also noted in the series of Komamura et al 84 This may be related to the concept that the presence of preinfarct angina is associated with smaller infarcts and a possible preconditioning-like effect and may correlate with collateral formation. 87 The no-reflow phenomenon was also linked to ventricular arrhythmias, 88 early congestive heart failure, 89 and even cardiac rupture.…”
Section: Clinical Presentationmentioning
confidence: 70%
“…82 New Q waves may appear, 83 and some of those patients may be diagnosed as having infarct extensions. In a study by Komamura et al, 84 9 patients with acute anterior myocardial infarction, early reperfusion, and probable no reflow were studied. The patients had continuous monitoring of the great cardiac vein blood flow.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Although it is difficult to explain the mechanism of this association, Komamura et al [30] have made a similar observation in patients treated with thrombolysis following acute myocardial infarction. They demonstrated that patients who suffered from pre-infarction anginal symptoms had shorter no-reflow duration and a better myocardial functional outcome.…”
Section: Discussionmentioning
confidence: 87%
“…Iwakura et al reported that more severe myocardial damage before recanalization is closely related to the no-reflow phenomenon in patients with successful coronary recanalization, 27 and other studies Previous studies have suggested that microvascular damage can develop even after recanalization. 28,29 Persistent hyperglycemia may have additionally increased the microvascular damage thereafter. Our results indicate that persistent hyperglycemia is independently associated with LV dysfunction before discharge, which is a strong predictor of long-term prognosis.…”
Section: Hyperglycemia and Severe Myocardial Damagementioning
confidence: 99%